Modeling and control of consumable DE-GMAW process. (October 2016) - Ming, Zhu; Chunkai, Li; Gang, Zhang; Yu, Shi; Ding, Fan; Jiankang, Huang
Abstract: A novel and highly efficient consumable double-electrode gas metal arc welding (consumable DE-GMAW) method was introduced. A non-linear mathematical model for the dynamic DE-GMAW process was developed by adopting the method of equivalent current path, according to the dynamic characteristics of coupled arc and the rule of wire melting. A multi-input multi-output (MIMO) control scheme was proposed and simulated because coupled welding parameters are complicated and the high welding current of DE-GMAW can lead to welding defects. This scheme controlled the bypass arc by adjusting the bypass wire feed speed and controlled the base metal current by adjusting the bypass current. To test the effectiveness of the MIMO control scheme, a welding experiment was conducted. Results showed that the MIMO control scheme was effective. The base metal current was controlled at a nearly constant level, the welding process was stable, and a good weld appearance was obtained.